2019
DOI: 10.1186/s13098-019-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin combined with metformin decreases glycemia and dyslipidemia, and increases paraoxonase activity in diabetic rats

Abstract: Background Combination of current antidiabetic agents with natural antioxidants to manage diabetes mellitus and its complications has appeared as an emerging trend. Curcumin, a yellow pigment isolated from Curcuma longa rhizomes, has gained attention due to its beneficial effects in controlling the disturbances observed in diabetes mellitus. The purpose of this study was to investigate if yoghurt enriched with curcumin and metformin, individually or as mixtures, ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 31 publications
2
44
1
Order By: Relevance
“…In the current study, there is a statistically significant direct correlation between area% of both caspase-3 and inter-acinar space after 2 weeks, this correlation could be explained as they are both sharing the same cause of their presence or absence which is the amount of produced ROS and the amount of oxidative stress produced by hyperglycemia [37] .…”
Section: Discussionsupporting
confidence: 52%
“…In the current study, there is a statistically significant direct correlation between area% of both caspase-3 and inter-acinar space after 2 weeks, this correlation could be explained as they are both sharing the same cause of their presence or absence which is the amount of produced ROS and the amount of oxidative stress produced by hyperglycemia [37] .…”
Section: Discussionsupporting
confidence: 52%
“…The first experiment related to therapeutic impact of curcumin was published in 1937 ( Zhou et al, 2011 ), and since then, much attention has been directed toward revealing the extraordinary pharmacological activities of curcumin. It has been reported that curcumin has valuable therapeutic and biological activities such as antioxidant ( Kharat et al, 2020 ), anti-inflammatory ( Sneharani, 2019 ), anti-diabetic ( Xia et al, 2020 ), hepatoprotective ( Dogaru et al, 2020 ), cardioprotective ( Hadi et al, 2019 ; Hallajzadeh et al, 2019 ; Kuszewski et al, 2019 ), neuroprotective ( Sturzu et al, 2019 ), anti-microbial ( Rai et al, 2020 ), anti-tumor ( Bahrami et al, 2019 ; Shabaninejad et al, 2020 ; Weng and Goel, 2020 ) and improving dyslipidemia ( Roxo et al, 2019 ) and ischemic-reperfusion ( Ahmed et al, 2019 ). Curcumin possesses great solubility in oil-based solutions.…”
Section: Curcumin: An Overview Of the Pharmacological Impacts And Limmentioning
confidence: 99%
“…A recent promising approach to treat hyperglycemia consists of combining the effects of curcumin and the ongoing antidiabetic agents, as observed in diabetic rats treated with a combination of curcumin and metformin. Specifically, this association improved hyperglycemia, dyslipidemia, and oxidative stress, increasing the activity of the antioxidant enzyme paraoxonase 1 (PON1), in diabetic rats [ 47 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%